The relationship of epicardial adipose tissue with hemodynamics and cardiopulmonary fitness in heart failure with preserved and reduced ejection fraction. (4th February 2022) - Pugliese, NR; De Biase, N; Mazzola, M; Paneni, F; Del Punta, L; Gargani, L; Mengozzi, A; Virdis, A; Nesti, L; Taddei, S; Flammer, A; Borlaug, BA; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background.  Recent evidence shows epicardial adipose tissue (EAT) acts as a paracrine organ and may directly alter myocardial function by exerting mechanical compression. Purpose. We evaluated EAT thickness through transthoracic echocardiography and investigated its relationship with cardiopulmonary fitness and cardiovascular haemodynamics at rest and during exercise in a population of heart failure (HF) patients with reduced (HFrEF) and preserved (HFpEF) ejection fraction. Methods. We prospectively enrolled 393 consecutive HF outpatients (205 HFrEF, 188 HFpEF) who had been referred to our hospital due to dyspnoea and/or effort intolerance, together with 44 healthy controls. We performed a resting state-of-the-art echocardiographic evaluation,  followed by combined cardiopulmonary-echocardiography exercise stress. Results.  EAT thickness was higher in HFpEF (median 8 mm, interquartile range [IQR] 4–12 mm) and progressively reduced in controls (median 5 mm, IQR 3–7 mm; p < 0.0001) and HFrEF (median 3 mm, IQR 2–6 mm).  In HFpEF,  EAT thickness was inversely correlated with peak oxygen consumption (VO2) and peripheral oxygen extraction (AVO2diff), while a direct association was observed for the same parameters in HFrEF (Figure 1). Furthermore,  EAT independently predicted peak VO2 and AVO2diff in HFrEF and HFpEF regardless of body mass index and waist circumference. These relationships were direct in HFrEF (standard regression coefficient [SRC] for peak VO2: 0.18,  p = 0.02; SRC for peak AVO2diff: 0.17,  p = 0.03) and indirect in HFpEF (SRC for peak VO2: -0.33, p < 0.0001; SRC for peak AVO2diff: -0.25,  p < 0.0001). As there are no definite cut-off values to define increased EAT, patients were divided based on the median EAT value (5 mm) of the overall population. Thinner EAT (≤5 mm) was associated with worse LV systolic dysfunction (peak average S') and remodeling (3D LV mass index) in HFrEF. In HFpEF,  on the other hand,  increased EAT (>5 mm) was related to worse right ventricular systolic dysfunction (3D right ventricular ejection fraction) and more severe left atrio-ventricular (left atrium reservoir strain/left ventricle global longitudinal strain) and right ventriculo-arterial (tricuspid annular plane systolic excursion/systolic pulmonary artery pressure) coupling (Figure 2). Conclusion. In HFpEF,  increased EAT thickness is associated with a worse hemodynamic profile and functional capacity. Conversely,  in HFrEF,  EAT thinning portends more advanced LV dysfunction and impaired cardiopulmonary fitness.